Gross And Histological Study On The Abattoir Ovaries Of Jaffrabadi Buffaloes - Kumar, Vishnudeo; Sharma , Anil (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The gross biometric and histological study was conducted on the ovaries of 30 Jaffrabadi buffaloes collected fresh from the local abattoir.The average weight of left and right ovaries was 4.08 ± 0.38 and 4.32 ± 0.26 g; average length 3.89 ± 0.13 and 4.14 ± 0.18 cm; average width 1.56 ± 0.06 and 1.62 ± 0.09 cm, and average thickness was 1.82 ± 0.08 and 1.90 ± 0.06 cm, respectively.There was no significant (P >0.05) difference in various gross biometric observations of left and right ovaries.The stroma of the ovary had distinct cortex and medulla. The ovarian surface was lined by simple cuboidal epithelium. The average height of epithelium was 4.26 ± 0.33 µm. The ovarian follicles were observed in different developmental stages distributed in the cortex. The average diameter of primordial, primary and secondary follicles was recorded as 26.37 ± 0.84 µm, 38.92 ± 0.66 µm and 74.25 ± 0.52 µm, respectively. The thickness of zona pellucida was 7.68 ± 0.37 µm and 6.40 ± 0.22 µm in secondary and tertiary follicles, respectively.
Keywords: Jaffrabadi buffalo; Abattoir ovaries; Biometry; Histology